Molecular Epidemiology and Spatial Distribution of a Waterborne Cryptosporidiosis Outbreak in Australia - Waldron, Liette S. (American Society for Microbiology, 2011)
Cryptosporidiosis is one of the most common waterborne diseases reported worldwide. Outbreaks of this gastrointestinal disease, which is caused by the Cryptosporidium parasite, are often attributed to public swimming pools and municipal water supplies. Between the months of January and April in 2009, New South Wales, Australia, experienced the largest waterborne cryptosporidiosis outbreak reported in Australia to date. Through the course of the contamination event, 1,141 individuals became infected with Cryptosporidium. Health authorities in New South Wales indicated that public swimming pool use was a contributing factor in the outbreak. To identify the Cryptosporidium species responsible for the outbreak, fecal samples from infected patients were collected from hospitals and pathology companies throughout New South Wales for genetic analyses. Genetic characterization of Cryptosporidium oocysts from the fecal samples identified the anthroponotic Cryptosporidium hominis IbA10G2 subtype as the causative parasite. Equal proportions of infections were found in males and females, and an increased susceptibility was observed in the 0- to 4-year age group. Spatiotemporal analysis indicated that the outbreak was primarily confined to the densely populated coastal cities of Sydney and Newcastle.